The Influence of Knowledge of Madrasah Teachers About Wadiah Savings Products and Interests Becoming a Customer at a Sharia Bank in Indramayu - Leli Kurniati (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2023)
The presence of Islamic banks in the midst of society is a solution or answer to the anxiety of prospective customers who want to obtain banking services without having to be familiar with usury, especially the Muslim community knows that usury is not permitted in Islamic law, therefore Islamic banking is here to answer that problem. However, the community's response was very diverse with the presence of Islamic banking, there were those who fully supported the presence of Islamic banking, there were those who refused and there were those who did not know that Islamic banking was present in their midst. community role model. One of the influential figures in society is that there are still many who have not used sharia banking services. This type of research uses a qualitative approach with the method used frequency distribution which aims to find out how much knowledge Madrasah Diniyah Takmiliyah Awaliyah Teachers have about Wadiah Savings Products and their interest in becoming customers at Islamic Banks, while data collection uses questionnaires or questionnaires which are distributed to all Village MDTA Teachers Jatisawit, Indramayu Regency. The conclusions that can be obtained are as follows: For a long time, Knowledge of Madrasah Diniyah Takmiliyah Awaliyah Teachers about Wadiah Savings is very knowledgeable at a percentage of 51.25%. Second , the interest of Madrasah Diniyah Takmiliyah Awaliyah teachers regarding wadiah savings products for their interest in becoming customers is very high because the percentage is 60%.